Orychophragmus violaceus and/or chicory forage affects performance, egg quality, sensory evaluation and antioxidative properties in native laying hens - W. Y. Zhao; Q. Q. Zhang; Y. F. Zhao; C. Chang; X. Wang; A. L. Geng (Animal Biotechnology)
Orychophragmus violaceus (OV) and chicory (Cichorium intybus L., CC) can be used as fresh or dry forage for animals. To determine whether OV and/or CC have beneficial effects on performance and egg quality, a total of 1212 28-wk-old Beijing You Chicken (BYC) laying hens with similar performance were randomly allocated to 4 groups with 3 replicate pens per group, and 101 birds per pen. The birds were fed a basal diet (control), the basal diet + OV (3.507 kg/d/pen), the basal diet + CC (2.525 kg/d/pen), and the basal diet + OV + CC (OVC, 1.7535 kg/d/pen OV + 1.2625 kg/d/pen CC) for 3 wks after one wk of adaptation. The results showed that egg-laying rate was not affected by OV, CC and OVC (p > 0.05), but weekly average egg mass was significantly increased by OV and CC (p < 0.05). The feed egg ratio in the CC group (2.82) was significantly lower than that in the other three groups (p < 0.05). The eggshell thickness (EST), albumen height (AH) and Haugh unit (HU) were decreased by OV and CC (p < 0.05); while yolk color (YC) was increased in the CC and OVC groups (p < 0.05). Egg grade was decreased by OV (p < 0.05). Sensory evaluation showed that there was a trend for increased YC in OV, CC and OVC (p = 0.089). Serum total protein was significantly lower in OV group than those in the control and CC group (p < 0.05); serum albumin content was significantly decreased in OV, CC and OVC groups (p = 0.006). Serum glutathione peroxidase activity in CC and OVC groups was significantly higher than that in the control group (p < 0.05). In conclusion, the present study suggests that CC had a better effect on the performance of the native laying hens than OV. The OV and CC affected egg quality, while YC was increased in CC and OVC groups. The OVC improved YC and serum antioxidative properties of native laying hens without affecting the performance.